A Nature-Inspired Crow Search Algorithm (CSA) Approach for Efficient Task Scheduling in Cloud Computing - Arvind Upadhyaya, Ramesh Thakur, Archana Thakur, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Most computer operations would take more time to complete in a VM since VMs arecomputational elements. Examining algorithms in nature that are used for scheduling tasks in cloudcomputing is the focus of